(untitled) (Biological Sciences - PJSIR, 2020)
Methanol, ethanol, acetone, ethyl acetate and hot water extracts of different parts (leaves, seeds, fruits and twigs fractions) of Psidium guajava L. were investigated for their antibacterial activities against 8 bacterial isolates. Inhibitory effects of P. guajava L. extracts have been screened by disc- diffusion method (Zone of inhibition, ZI), activity index (AI) and minimum inhibitory concentration (MIC) determination. Ciprofloxacin antibiotic was used as standard for P. guajava L. antimicrobial activity comparison. From the ZI, AI and MIC values, methanolic and hot water extracts of twigs < 1cm diameter were the most potent against all tested micro-organisms by showing the highest ZI and AI value and the lowest MIC values. Whereas, no inhibitory activity was recorded for both seeds and fruits extracts using all tested solvents. These observations make this plant a potential source that can be used in management of bacterial infections. Moreover, methanolic and hot water extracts of twigs < 1cm required further in depth study.